The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11528-016-0070-3
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Open Textbooks Analytics System

Abstract: In the last few years, open textbook development has picked up dramatically due both to the expense of commercially published textbooks and the increasing availability of high-quality OER alternatives. While this offers a tremendous benefit in terms of lowering student textbook costs, the question remains, to what extent (if any) do open textbooks influence the amount and method in which students engage with their open textbooks. The answers to these questions should provide useful new insights for all involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
5
0
3
Order By: Relevance
“…This may point out that academic electronic books have had a positive impact on increasing the achievement of higher education students due to they gave them the capability to arrive at a digital transcribe of printed books, and maybe also they benefited from the features included like search option, interactive elements, easily updates, create notes on the text...etc. This result is consistent with previous studies ( Brown (2016) , Christie 2011 ; Ciampa, 2012 ; Hwang and Lai 2017 ; Jones and Brown, 2011 ; Lokar, 2015 ; Prasad et al. 2016 ; Phadung and Dueramae 2018 ; Slavin 2008 ; Turel and Sanal 2018 ; Wu et al., 2014 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may point out that academic electronic books have had a positive impact on increasing the achievement of higher education students due to they gave them the capability to arrive at a digital transcribe of printed books, and maybe also they benefited from the features included like search option, interactive elements, easily updates, create notes on the text...etc. This result is consistent with previous studies ( Brown (2016) , Christie 2011 ; Ciampa, 2012 ; Hwang and Lai 2017 ; Jones and Brown, 2011 ; Lokar, 2015 ; Prasad et al. 2016 ; Phadung and Dueramae 2018 ; Slavin 2008 ; Turel and Sanal 2018 ; Wu et al., 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, they tend to utilize electronic books rather than traditional paper books and the teaching process is more interesting, enticing and inspiring for them to learn and to teach. In addition to that, the electronic books supporting the faculty staff members in their teaching of the students in the university ( Brown 2016 ; Christie 2011 ; Ciampa 2012 ; Embong et al., 2012 ; Gelderblom et al., 2019 ; Hwang and Lai, 2017 ; Jones and Brown, 2011 ; Liaw and Huang 2014 ; Lim and Hew 2014 ; Letchumanan and Tarmizi 2011 ; Prasad et al. 2016 ; Plangsorn and Poopan 2017 ; Phadung and Dueramae 2018 ; Slavin 2008 ; Turel and Sanal 2018 ; Wu et al., 2014 ; Yalman 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they have been said to encourage collaboration and interaction among students (Kiryakova, Angelova, & Yordanova, 2014;Brigham, 2015;Wang, 2015;. Further, these technologies have the potential to provide instant feedback about students' learning (Coca & Slisko, 2013;Elliott, 2015;Hussein, 2015;Wang, 2015;Fotaris, Mastoras, Leinfellner, & Rosunally, 2016;Chaiyo & Nokham, 2017). According to Brigham (2015), instant feedback coupled with collaborative learning can satisfy the requirements of learners, particularly, millennials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unsurprisingly, the outcome was the shift to a new generation of web-based applications(such as Kahoot, Socrative, Quizizz, and Quizlet) that provide more interactive platforms with tempting graphical and audio effects which add game elements and turn quizzes into a game (Wang, 2015;Wang, Zhu, & Saetre, 2016). Several studies have reported significant effects of these applications on students' perceptions and academic performance (Coca &Slisko, 2013;Elliott, 2015;Hussein &Picciano, 2015;Wang, 2015;Fotaris, Mastoras, Leinfellner, &Rosunally, 2016;Wang & Lieberoth, 2016;Chaiyo & Nokham, 2017). Yet, more research is needed to explore the effect of each of the game elements added to the quizzes on student's perception (Heong, Filippou, and Cheong, 2014;Wang and Lieberoth, 2016) and especially in the EFL classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental work was guided by our earlier work proposed in (Prasad, Totaram, & Usagawa, 2016) describing a framework for development of an open textbooks analytics system, as shown in Figure 1. This framework supports textbooks in the EPUB format, a format that has become the international standard for digital books.…”
Section: Conceptual Frameworkmentioning
confidence: 99%